Alternative learning system (ALS) of division of Pangasinan I : basis for proposed work and financial plan - Garcia, Renato R. (San Carlos City, Pangasinan : [s.n.], 2013)
The research looked into the implementation of Alternative Learning System (ALS) in the Division of Pangasinan I during calendar year 2010-2012 as basis for a proposed work and financial plan. The study was conceptualized as having a particular role in catering the needs of ALS implementers in improving their performance. The research was initiated to make documentary analysis on submitted reports from the ALS Division Office to: (a) determine the ALS programs implemented; (b) identify programs implemented under different schemes of delivery; (c) ascertain the products of implementation; (d) assess the management and administrative support; (e) determine problems encountered, and (f) look at the best practices of program implementation. The findings show that seven out of twelve ALS programs were implemented under DepEd Delivered such as Accreditation and Equivalency, Basic Literacy Program and Family Basic Literacy Program. Under DepEd Procured; Balik-Paaralan Para sa Out-of-School Adults, ALS-Gabay Aral sa Pamayanan, and Non-DepEd is Informal Education. The participation rate is low, survival rate is low, and achievement rate is poor. On the other hand, absorption rate is high. The management and administrative support has identified a limited number of ALS implementers and the ratio of ALS implementers to learners is high. Number of makeshift community learning centers used are increasing. Lack of permanent community learning centers as prevalent problem, while, writing project proposal is identified as the best practice, Therefore, out of the twelve programs of ALs, seven were implemented; the products of implementation is poor; lack of management and administrative support system and lack of permanent community learning centers as prevailing problem, while writing project proposal is best practice. With the foregoing findings and conclusion, the proposed work and financial plan be adopted and used by ALS of Division of Pangasinan for programs not yet implemented and improve program implementation.
Bibliography: pages 147-151.
CHED-La Union
Keywords: Alternative learning system